CHARACTERISTICS OF FISHING AND THE NUTRITIONAL CONTRIBUTION OF THE FISHERY RESOURCE IN THE COMMUNITY ‘SANTA ROSA DEL ARIPARI' FROM THE CAHUAPANAS RIVER BASIN - RYNABY-RENGIFO, Jhonatan (2022)
Despite its importance in the local economy and food supply, the fishing carried out by riverside communities has been little studied. This paper presents the main characteristics of fishing in Lake Aripari based on the analysis of fish landing records. Between April 2018 and February 2019, species' richness and composition, landed biomass, catch per unit effort (CPUE) by hydrological periods, and the nutritional contribution of species destined for human consumption were evaluated. Forty-seven species were recorded, grouped into 23 families and 9 orders, with the Pimelodidae family being the most diverse (6 species). Species' richness was higher during the dry season, dominated by species of local migration and piscivorous habits. The total landings amounted to 10 650.7 kg, where 14 species accounted for 85.0% of the biomass. Sixty-seven percent of the biomass was for sale, with more than 57% being landed in crescent. The mean annual CPUE was 0.30 kg/hp (SD = 0.18), with the lowest catches in the crescent season (KW, p-value < 0.05). The oxbow lakes were the aquatic environments with the highest CPUE (KW, p-value < 0.05). Boquichico and llambina stand out for their contribution in protein, phosphorus, iron, potassium, and omega-3. The results show that fishing in Lake Aripari is carried out on a small scale in different aquatic environments where a diverse group of fish are caught with different fishing materials, making this an important and deeply rooted activity in the community.